El lenguaje oral y las habilidades comunicativas en los estudiantes de séptimo año de educación general básica de la Unidad Educativa Roberto Alfredo Arregui Chauvin de la ciudad de Guaranda en el periodo 2021-2022. - Gutiérrez Guamán, Stefany Gabriela (2022)
Communication skills are the ways in which human beings use language for different purposes: to communicate, learn and think. These are fundamentally four: listening, speaking, reading and writing. Cognitive theories of learning were taken as a basis, since they focus on the study of cognitive and socialized processes for the construction of learning. The research problem was raised and formulated: How does oral language stimulate the development of communication skills in seventh- year general basic education students at the Roberto Alfredo Arregui Chauvin educational unit? The parameters to identify are: social and educational behavior, to seek improvement at the level of reading and neurolinguistic expression, the skills to be considered in children are represented through the development of the educational intervention plan, identifying a specific structure that It consists of 5 phases: observation, implementation, evaluation, proposal for improvement and exposure, which are the set to carry out the analysis and interpretation of the results of the 10 questions described in a survey and in the interview. When identifying the problem that the research refers to, the dependent and independent variable is taken into account, which describes both websites and digital pedagogical tools, which are found within the curricular mesh that the Seventh Year Parallel "C" general basic education Students have. Of the Educational Unit Roberto Alfredo Arregui Chauvin”, for which it acts directly with teachers and students, in a context of narrative, cultural, historical, legends and fables, the latter being the ones that most attract the attention of the students. young people, so a space must be created for the student to obtain other types of texts that are within their preferences, as long as they are suitable for their age. When establishing the margin of the results, evaluation instruments such as the survey, interview, graphs and tables must be taken into consideration, where the management of the research can be identified, since the strategies used for the field of education must always be governed in consideration of the age and learning system of the students. Due to the pandemic, the activities were carried out virtually, providing an enhancement of the research, since the mundo primary website could be shared, through the ZOOM platform, this application allows massive talks to be held in real time, evidencing so it is feasible to have a good quality reading comprehension through digital pedagogical tools. Within the evaluation model, it is proposed through a hierarchical order, where the student will improve their level of reading comprehension through texts found in the sixth-grade book, being a substantial source of information, without neglecting the website readings recognized as a student's virtual library, when taking active breaks.